Arachnoid Cyst of the Cavum Velum Interpositum in a Septuagenarian: Radiological Features and Differential Diagnosis. Issue 2 (April 2014) - Rajesh, S; Bhatnagar, Shorav; Chauhan, Udit; Gupta, Shailesh; Agarwal, Nitesh; Kasana, Vivek
The cavum velum interpositum (CVI) is a thin, triangular-shaped cerebrospinal fluid (CSF)-filled space between the lateral ventricles that lies below the fornices and above the third ventricle. It is a normal variant seen in premature and newborn infants and usually disappears with brain maturation. CVI is rarely seen in adults as a persistent primitive structure. Although moderate cystic dilatation of the CVI may sometimes be observed, a true large cyst is extremely rare with only a handful of reported cases, mostly in children and adolescents. We describe the case of CVI arachnoid cyst diagnosed on imaging in a septuagenarian with the complaint of occasional headaches.